Eco-hydrological responses of the Black Dragon fire in three forested basins in the Daxing'an Mountains, northeast China. (December 2022) - Liu, Wenbin; Sun, Fubao; Ju, Cunyong; Zhang, Xuanze; Cai, Tijiu; Lan, Zhiyang
Highlights: Ecohydrological responses to the 1987 fire were re-examined in three forested basins. A significant decline in most ecohydrological variables was detected in the 1987 fire. The hydrological systems need longer time to recover from fire than NDVI, LAI and GPP. Abstract: Understanding how bushfire affects basin-wide ecohydrological processes is critical for ecological restoration and water supply. However, the mechanisms responsible for post-fire streamflow remain poorly explored in forested basins of China due to complex scale-dependent relationships between fire-induced forest changes and ecohydrological processes, lack of reasonable design of paired watershed experiments, and especially data scarcity. Here, we re-examine ecohydrological responses of the Black Dragon fire (one of the largest and most damaging forest fires on record globally) on an annual scale in three forest basins (two fire-impacted basins, namely Emuer and Pangu, and a nearly unimpacted basin, Huma) in the Daxing'an Mountains using multiple most recent datasets and methods. We found that the Black Dragon fire decreased annual- and basin-averaged vegetation leaf area, evapotranspiration, interception loss, transpiration, soil moisture, runoff, and discharge capacity in 1987 in the two fire-impacted basins compared with the unimpacted basin. The annual- and basin-averaged evapotranspiration (runoff) did not reduce (increase) as much as that expected with decreased LAI given the precipitation amount in 1987 in the two fire-impacted basins, which properly linked to the quick postfire regrowth of vegetation in the growing season. Vegetation leaf area and productivity can quickly recover in the following two to three years postfire, but the hydrological systems need more than 10 years to adapt this disturbance. These findings improve the understanding of ecohydrological responses to bushfire disturbance and provide scientific evidence for ecological protection and water resources management under intensified natural and anthropogenic disturbances.